Antigenic and immunogenic characterization of infectious bronchitis virus strains isolated in China between 1986 and 1995 - Wu, Z. Q. (Avian Pathol, 2007)
Eight strains of infectious bronchitis virus (IBV) were isolated between 1986 and 1995 from broilers and layers at eight different farms in four provinces in China. The viruses were isolated from flocks which suffered from either respiratory disease or nephritis and the majority had not been vaccinated against IBV. Six strains were shown by monoclonal antibodies to differ from H120, Connecticut and Arkansas 99 strains of IBV and also to differ from each other. Four of these strains were serotyped; one (NRZ) was of the Massachusetts serotype, three (HV, NB-90 and TJ) shared a degree of antigenic similarity and were of a serotype that differed from Massachusetts and Connecticut. NB-90 was similar to both Gray and T strains whereas TJ shared some similarity with the T strain. Four strains, HV, NB-90, YY and TJ induced 33, 47, 60 and 90% mortality, respectively, in 3-week-old specific pathogen-free chickens. Clinical signs and post-mortem findings were identical to those induced by the nephropathogenic T strain. Chickens vaccinated with H120 strain, and then challenged with four highly pathogenic strains HV, NB-90, YY and TJ were not protected as determined by both virus isolation and mortality. The results show that highly pathogenic IBV strains which induce clinical nephritis occur frequently in poultry flocks in China. They also confirm field observations on the lack of protection by currently used IB vaccines of the Massachusetts serotype against challenge with these nephropathogenic strains.